Handbook of computational intelligence in manufacturing and production management - Laha, Dipak; Mandal, Purnendu; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book focuses on new developments in computational intelligence in areas such as forecasting, scheduling, production planning, inventory control, and aggregate planning, among others. It provides cutting-edge knowledge on information technology developments for both researchers and professionals in fields such as operations and production management, web engineering, artificial intelligence, and information resources management"--Provided by publisher.
15. Planning and deployment of dynamic web technologies for supporting e-business / John Hines -- 16. Web-based decision support system : concept and issues / Rajib Goswami, Pankaj Barua -- 17. Independent component analysis and its applications to manufacturing problems / Xian-Chuan Yu ... [et al.] -- 18. Swarm intelligence in production management and engineering / Swagatam Das, Amit Konar -- 19. Artificial neural network and metaheuristic strategies : emerging tools for metal cutting process optimization / Indrajit Mukherjee, Pradip Ray -- 20. Intelligent laser scanning of 3D surfaces using optical camera data / A. Denby ... [et al.] -- 21. Using data mining for forecasting data management needs / Qingyu Zhang, Richard Segall -- 22. Supply network planning models using enterprise resource planning systems / Sundar Srinivasan, Scott Grasman -- 23. Modeling and analysis for production performance : analysis of U.S. manufacturing companies / Purnendu Mandal, Enrique Venta.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 29, 2010).
Keywords: Production management -- Technological innovations; Computational intelligence; AI-based random search optimization approach; Analytical hierarchal processes; Computational intelligence in financial functions; Condition monitoring using computational intelligence; Data mining applications to manufacturing; Demand forecasting of short-life-span products; Dynamic web technology support of e-business; Dynamics supply networks; Enterprise resource planning systems; Evolutionary computing; Fuzzy set processes; Heuristic and metaheuristic development; Independent component analysis; Integrated manufacturing applications; Intelligent laser scanning; Management decision making; Supply chain behavior; Swarm intelligence; System archetypes modeling; Web-based decision support systems; Electronic books